1991
DOI: 10.1111/j.1445-5994.1991.tb01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases insulin sensitivity and basal glucose clearance in Type 2 (non‐insulin dependent) diabetes mellitus

Abstract: The effects of metformin on glycaemia, insulin and c-peptide levels, hepatic glucose production and insulin sensitivity (using the euglycaemic, hyperinsulinaemic clamp) were evaluated at fortnightly intervals in 9 Type 2 diabetic patients using a stepwise dosing protocol: Stage 1--no metformin for four weeks; stage 2--metformin 500mg mane; stage 3--metformin 500mg thrice daily; stage 4--metformin 1000mg thrice daily. Results are expressed as Mean +/- SEM. Fasting blood glucose decreased from basal values (9.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 14 publications
0
45
0
2
Order By: Relevance
“…The lack of effect of metformin in the presence of insulin is consistent with the negative results of many of the hyperinsulinemic euglycemic clamp studies (18 -22, 45). However, many studies have shown significant improvements in insulin-mediated glucose disposal with metformin (3,7,10,13,14,16,17,20,23,45). Metformin activates AMPactivated protein kinase (7), increases hepatic expression of glucokinase and liver-type pyruvate kinase, and decreases expression of glucose-6-phosphatase, phosphoenolpyruvate carboxykinase, carnitine palmitoyltransferase-I, and mito-FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect of metformin in the presence of insulin is consistent with the negative results of many of the hyperinsulinemic euglycemic clamp studies (18 -22, 45). However, many studies have shown significant improvements in insulin-mediated glucose disposal with metformin (3,7,10,13,14,16,17,20,23,45). Metformin activates AMPactivated protein kinase (7), increases hepatic expression of glucokinase and liver-type pyruvate kinase, and decreases expression of glucose-6-phosphatase, phosphoenolpyruvate carboxykinase, carnitine palmitoyltransferase-I, and mito-FIG.…”
Section: Discussionmentioning
confidence: 99%
“…However, particularly with long-term therapy, metformin provokes increases in insulin-stimulated glucose disposal [6][7][8][9][10], presumably at least partly by increasing glucose utilisation in muscle. Moreover, in vivo treatment of rats with metformin provokes increases in insulin-stimulated glucose transport, as measured in isolated skeletal muscle preparations [11,12], and metformin itself increases 2-deoxyglucose uptake in cultured myocytes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin acts to reverse two of the above defects via three mechanisms: (1) reduction in hepatic glucose production, (2) reduction in intestinal glucose absorption, and (3) increased insulin sensitivity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%